2019
DOI: 10.1039/c9nr04412d
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of a purely electronic two-dimensional lattice at the interface of TMD/Bi2Se3 heterostructures

Abstract: Vertically-stacked 2D materials produce new physics from interfacial orbital interactions and the moiré superlattice, possibly inducing the formation of a robust real-space, non-atomic charge lattice at room temperature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 46 publications
2
39
0
Order By: Relevance
“…Recently, moiré pattern with periodicity of ~ 8.9 nm has been observed by the transmission electron microscopy (TEM) at the graphene/Al (111) interface [29]. A non-atomic lattice formed by interlayer coupling induced charge redistribution in Bi2Se3/TMD heterostructures has been revealed by high-energy selected area electron diffraction (SAED) as well [6]. Our experiment is a very first attempt to investigate the moiré modulation effects to the electronic properties of topological insulators.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, moiré pattern with periodicity of ~ 8.9 nm has been observed by the transmission electron microscopy (TEM) at the graphene/Al (111) interface [29]. A non-atomic lattice formed by interlayer coupling induced charge redistribution in Bi2Se3/TMD heterostructures has been revealed by high-energy selected area electron diffraction (SAED) as well [6]. Our experiment is a very first attempt to investigate the moiré modulation effects to the electronic properties of topological insulators.…”
Section: Resultsmentioning
confidence: 99%
“…Moiré pattern results from the overlap of two lattices with a lattice mismatch or a small-angle twist [1]. Moiré system can induce exotic electronic properties such as correlated states in twisted bilayer graphene (TBG) [2][3][4][5], Hofstadter's butterfly pattern in graphene/hexagonal boron nitride (hBN) heterostructures, interlayer coupling induced charge redistribution [6] and spatially dependent band gap in transition metal dichalcogenides (TMD) [7]. In addition to graphene, hBN and TMD, another family of moiré superlattice can be found in topological insulators (TIs) [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…the manner in which the lattice points are stacked on top of each other even in untwisted self-similar 2D layers, could also play a role in the properties of the resulting heterostructures, but is intentionally not a topic covered in this review). Indeed, the diverse variety of atomically-thin 2D materials provide unique opportunities for creating new nanostructures through vertical and horizontal stacking with virtually limitless possibilities and, as a result, the intense interest in exploring the science and engineering of such 2D structures has continued unabated since the discovery of graphene, with structurally-inspired names such as van der Waals solids or heterostructures, functionallyinspired names such as electron quantum metamaterials, [46][47][48][49] and with a unique area of focus being moiré superlattices, [50][51][52] which has revealed a diverse range of novel quantum phenomena and phases, often related to the specific way the layers are twisted with respect to each other. The twist angle (i.e., the relative angle between layers) 53 determines the new periodicity (i.e., moiré pattern) formed between the individual crystalline layers, while the interlayer coupling determines the magnitude of electron-particle interactions, 54 hybridization, charge redistribution, 55 and lattice reconstruction.…”
Section: Introductionmentioning
confidence: 99%
“…[80] Comparing with monolayer 2DMs, van der Waals-stacked heterojunctions constructed by different types of 2DMs have drawn much attention in recent years because of their advantages as alternative light-emitting materials. [72,[168][169][170][171] First, the energy of interlayer excitons in heterojunctions (type-II band alignment) can be smaller than that of intralayer excitons, leading to a redshift in emission. Recent work showed that the emission wavelength of MoS 2 /WSe 2 heterojunction was up to 1122.5 nm [172] that is longer than that of the intralayer excitons' emission wavelength.…”
Section: Light Sourcesmentioning
confidence: 99%